Measuring spatial accessibility of public libraries using floating catchment area methods: A comparative case study in Calhoun County, Florida - Samuel Takyi; Richard B. Antwi; Eren Erman Ozguven; Onur Alisan; Mahyar Ghorbanzadeh; Marcia Mardis; Faye Jones (Transportation Research Interdisciplinary Perspectives, 2023)
Public libraries are critical facilities that provide a variety of essential services to the public such as providing access to information, resources, sheltering and gathering space during natural disasters such as hurricanes, especially in rural areas. Although several researchers have focused on accessibility to libraries, these works only consider the travel time or distance between communities and libraries, which may be an inadequate way of analyzing their accessibility. To provide a more realistic analysis, this paper uses the Enhanced Two-Step Floating Catchment Area (E2SFCA), and Three-Step Floating Catchment Area (3SFCA) methods to measure the accessibility of U.S. Census block groups to public libraries within Calhoun County, Florida, a rural county hit hard by Hurricane Michael in 2018. These methods define the service areas of libraries by a threshold travel time while accounting for their availability by the demand surrounding these facilities. Findings indicate there are disparities in accessibility among census block groups. The ones with higher population densities have lower accessibility to libraries which indicates that accessibility does not depend only on travel time as determined by other research works but also on the capacity of the service area. To improve the accessibility of public libraries in rural counties, this study recommends the creation of service areas for libraries in order to provide better service to the public, including vulnerable populations such as older adults.